Hubungan antara Product Knowledge dengan Kinerja Karyawan Divisi Perkembangan KSPPS TAM Nganjuk - Arethusa, Zana Chobhita; Indrarini, Rachma (Universitas Negeri Surabaya, 2019)
The aim of this research is to test the relation between product knowledge and employee performance of development division Koperasi Simpan Pinjam dan Pembiayaan Syariah (KSPPS) Tunas Artha Mandiri (TAM) Nganjuk. This research was conducted using quantitative method with associative approach. Number of population that taken are 35 respondents which employee of development division. Data collection techniques that used in this research is questionnaire that calculates with likert scale and Indikator Penilaian Kinerja (IPK) employee of development division document 2018 period which then processed and analyzed with application SPSS Statistics Version 23. The result of this research shows that product knowledge have a weak relation with employee performance of development division.